Evaluation of the Effect of Combined Hand Therapy and Local Steroid Injection for the Treatment of Idiopathic Carpal Tunnel Syndrome - Gamal M. Saied; Ahmed M. Kensarah; Ragia M. Kamel (Journal of King Abdulaziz University: Medical Sciences, 2023)
Oral non-steroidal anti-inflammatory drugs and local steroid injection are the standard treatment of carpal tunnel syndrome. The objective of this study is to reassess the efficacy of this non-surgical treatment. One hundred and nineteen patients with carpal tunnel syndrome were categorized into 3 groups (based on symptom severity inferred by physicians). Group I included 68 patients, Group II 31 and Group III 20 patients, respectively. All patients received nonsteroidal anti inflammatory drugs. The first group received in addition to hand therapy, wrist splinting, while intra-canal injection of triamicinolone acetonide was added to patients of group II. Follow up was for 6 months. Assessment was for the degree of pain relief, and improvement in hand grip strength. Most patients were females, having right hand disease. After 6 months, results were as follows: In group I, 36 % had less pain, but with no affect on hand grip strength. In group II, less pain was found in 75% of patients with 12.76% increase in hand grip strength. In group III, the response was minimal. The study demonstrates that in carpal tunnel syndrome, hand therapy with wrist splinting is appropriate for early cases, and that local steroid injection potentiates its response.